PELATIHAN BAHASA JAWA RAGAM KRAMA INGGIL UNTUK MENINGKATKAN KOMPETENSI BERBAHASA MASYARAKAT DI DUSUN CEPOKOSARI, PIYUNGAN, BANTUL - Luwiyanto Luwiyanto; Krisna Pebryawan; Bayu Indrayanto; Ike Anisa (WIDHARMA - Jurnal Pengabdian Widya Dharma, 2026)
The krama inggil variety of the Javanese language is one of the forms of unggah-ungguh basa (speech level system) that reflects the values of politeness and respect in Javanese culture. However, its use in daily communication has increasingly declined due to the dominance of the Indonesian language and the decreasing practice of using polite Javanese in family and community environments. This condition is also found among thecommunity members of Dusun Cepokosari RT 6, Cepokojajar, Piyungan District, Bantul Regency, who still experience difficulties in selectingappropriate vocabulary, constructing sentences, and applying speech levels according to communication contexts. This community service program aimed to improve the community’s competence in using the krama inggil variety of Javanese while fostering awareness of the importance of preserving Javanese language and culture. The program employed a participatory-educational approach consisting of several stages: preparation, training implementation, practice and mentoring, and evaluation. The participants involved 20 people consisting of youth organization members and local community members. The training materials covered Javanese unggah-ungguh basa, basic krama inggilvocabulary, sentence construction, and contextual conversation practices. The evaluation results showed an improvement in participants’ abilities,with the average score increasing from 57.75 in the pre-test to 88.38 in the post-test, representing an increase of 30.63 points. After the training, 80% of participants achieved a very good category, while 20% were categorized as good. These results indicate that practice-based training and mentoring are effective in improving participants’ skills in using the krama inggil variety of Javanese while simultaneously supporting thepreservation of Javanese cultural communication values.